Developing a Model for Choosing Coaches of Basketball National Teams - Nahid Adibpour; Mahsa Hosseini; Habib Honari (Shahid Bahonar University of Kerman, 2021)
The purpose of this study was to identify and to prioritize the most important criteria to choose qualified coaches for the basketball national teams in Iran based on the perspective of sport experts, managers, basketball coaches, and elite players. Method used in this research was descriptive and survey kind. 135 participants were studied through random sampling approach according to the Morgan table. After collecting the questionnaires, 110 samples were qualified for further investigations. The data was analyzed with both descriptive statistics and inferential statistics including Kolmogorov-Smirnov test, Friedman test for finding the priority of criteria and analysis of variance test, using SPSS software. The order of the eight identified treats include "Personality and Cognitive Features, Emotional and Humanistic Characteristics, Social Characteristics, Managerial Skills, Scientific Knowledge and Expertise, Coaching Experiences, Demographic and Personal Characteristics, and Basketball Sport Skills". Personality and cognitive features of a coach with mean rank of 6.35 is the most important factor to choose a coach (X2= 61.39, p <0.01) among the eight main criteria. Significant differences were obvious only on the last two items including "Sport skills" and "Personal characteristics" among male and female subjects.